2013
DOI: 10.1016/j.urology.2012.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementation With Hydrogen-rich Water in Patients With Interstitial Cystitis/Painful Bladder Syndrome

Abstract: Results: A total of 30 participants (29 female, 1 male, age 64.0 ± 14.8 years) were enrolled into the study and two cases (all females) were withdrawn from the study.The score of bladder pain was significantly reduced in both groups. However, the effect of hydrogen-rich water on symptoms was not significantly different from placebo, although the supplementation with hydrogen-rich water was extremely effective in improving bladder pain score in 11 % of the patients. Conclusions:The results of the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…A C C E P T E D ACCEPTED MANUSCRIPT 18 with recent studies that molecular hydrogen protects against neuronal apoptosis by improving mitochondrial dysfunction by suppressing ROS-activated caspase signaling [38]. The FoxO3a protein is also thought to be involved in mitochondrial protection by increasing a wide range of mitochondrial antioxidant enzymes [39].…”
Section: A N U S C R I P Tmentioning
confidence: 96%
See 1 more Smart Citation
“…A C C E P T E D ACCEPTED MANUSCRIPT 18 with recent studies that molecular hydrogen protects against neuronal apoptosis by improving mitochondrial dysfunction by suppressing ROS-activated caspase signaling [38]. The FoxO3a protein is also thought to be involved in mitochondrial protection by increasing a wide range of mitochondrial antioxidant enzymes [39].…”
Section: A N U S C R I P Tmentioning
confidence: 96%
“…Moreover, some studies reported HRW can significantly reduce several neurodegenerative diseases and this is associated with increased defense to oxidative stress [16]. Recently, clinical trials have also proven the benefits of HRW in attenuating oxidative stress and inflammation in patients [17,18]. Particularly, oral intake of HRW displays anti-neurotoxicity effects by regulating the oxidant and antioxidant status of rats [19].…”
Section: Introductionmentioning
confidence: 99%
“…Pronounced effects in human studies are observed especially in oxidative stress-mediated diseases, including cerebral infarction [45], liver carcinoma [26], chronic inflammation in hemodialysis patients [38], inflammatory and mitochondrial myopathies [22], metabolic syndrome [36], diabetes mellitus [24], Parkinson's disease [61] and rheumatoid arthritis [21]. One study reported no beneficial effects of H 2 in urology patients [32]. The summary of the human studies is presented in • ▶ Table 1.…”
Section: Overview Of the Medical Use Of Hydrogen ▼mentioning
confidence: 99%
“…To provide evidence of the safety of H 2 application in humans, several studies assessed the possible side effects of hydrogenrich water on clinical chemistry parameters and subjectively reported adverse events of intervention. The majority of the studies revealed no side effects of hydrogen-rich water administration in humans [21,26,32,46,48,49,61]. Nakao et al [36] found minimal disturbances in liver enzymes and biochemical profiles in subjects with potential metabolic syndrome receiving up to 2 L/day of hydrogen-rich water.…”
Section: Adverse Effects Of Molecular Hydrogen ▼mentioning
confidence: 99%
“…They were treated with H 2 -enriched water or placebo for 8 weeks. Although hydrogen intake did not change significantly the IC/PBS clinical scores during the study, there were improvements in pain perception in 11% of the patients [294].…”
Section: Hydrogen In Inflammatory Diseasesmentioning
confidence: 70%